CLINAMEN, OR THE AUTO-REJECT FOR “POSTHUMAN” FUTURES - Goh, Irving (Reject, 2014)
In following the animal in the last two chapters — first the animal-messiah in Cixous, and then becoming-animal in Deleuze and Guattari — one could say that the question of therejecthas progressively taken on a “posthuman” contour, especially if one follows Cary Wolfe’s “posthumanism,” or Rosi Braidotti’s “posthuman critical theory” (even though, as I will explicate in a while, one should heed Braidotti’s “posthumanism” only in limited ways). According to Wolfe inWhat is Posthumanism?,the animal question — particularly that which Derrida inL’Animal que donc je suistakes as its point of departure — is what “posthuman” discourse, if it